2008
DOI: 10.1002/zoo.20180
|View full text |Cite
|
Sign up to set email alerts
|

Tongue twisters: feeding enrichment to reduce oral stereotypy in giraffe

Abstract: Stereotypic behavior has been well-studied and documented in a variety of animals including primates, carnivores, and domesticated ungulates. However, very little information is known about stereotypic behavior of captive exotic ungulates. Giraffe have been found to perform a wide range of stereotypic behaviors. According to a survey of zoological institutions, oral stereotypies, specifically the licking of nonfood objects are the most prevalent stereotypic behaviors observed in giraffe. Their performance appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Time spent eating routine diets was significantly associated with reduced performance of oral stereotypies, and this relationship was strengthened when combined with time spent participating in GFPs. This relationship supports the hypothesis that increased time spent feeding reduces time spent performing oral stereotypies [Koene, ; Tarou et al, ; Fernandez et al, ]. Guest feeding programs, in combination with increased feeding duration of routine diets, can significantly reduce performance of oral stereotypic behavior, reinforcing the proposition that these programs can serve as environmental enrichment for captive giraffes.…”
Section: Discussionsupporting
confidence: 75%
“…Time spent eating routine diets was significantly associated with reduced performance of oral stereotypies, and this relationship was strengthened when combined with time spent participating in GFPs. This relationship supports the hypothesis that increased time spent feeding reduces time spent performing oral stereotypies [Koene, ; Tarou et al, ; Fernandez et al, ]. Guest feeding programs, in combination with increased feeding duration of routine diets, can significantly reduce performance of oral stereotypic behavior, reinforcing the proposition that these programs can serve as environmental enrichment for captive giraffes.…”
Section: Discussionsupporting
confidence: 75%
“…The active animals were recorded as vigilant while feeding or standing. Considering that giraffe spend half of their time feeding (e.g., Fennessy, ; Fernandez, Bashaw, Sartor, Bouwens, & Maki, ), the need for food intake continues during the night and requires a resting site offering sufficient feeding possibilities. Young and Isbell () reported that the choice of feeding sites for giraffe during the day depends on age, sex, and group constellation.…”
Section: Discussionmentioning
confidence: 99%
“…The stimuli provided typically allow or encourage behaviour patterns that the animals are naturally motivated to perform (see e.g. [6]), examples including substrates in which pigs can root [7] and giraffe feeders that require tongue manipulation [8]. Many studies across diverse species, both wild and domesticated, demonstrate the success of enrichment for improving wellbeing: animals are often highly motivated to access enrichment items (e.g.…”
Section: Introductionmentioning
confidence: 99%